Contribution to the knowledge of the fossil subgenus Nestormeus Godunko, 2004 (Ephemeroptera: Heptageniidae: Ecdyonurus) from the Baltic amber (Eocene) - Godunko, Roman J. (Zootaxa, 2007)
A female imago of Ecdyonurus groehnorum sp. nov. from the Baltic amber (Eocene) is described and illustrated. We have placed this new species within the early described subgenus Nestormeus Godunko, 2004 because of the presence of the short, curved lateroparapsidal sutures on the mesonotum, which are noncontiguous with the medioparapsidal sutures.